2003
DOI: 10.1128/jb.185.18.5573-5584.2003
|View full text |Cite
|
Sign up to set email alerts
|

Genome Diversification in Phylogenetic Lineages I and II ofListeria monocytogenes: Identification of Segments Unique to Lineage II Populations

Abstract: Thirteen different serotypes of Listeria monocytogenes can be distinguished on the basis of variation in somatic and flagellar antigens. Although the known virulence genes are present in all serotypes, greater than 90% of human cases of listeriosis are caused by serotypes 1/2a, 1/2b, and 4b and nearly all outbreaks of food-borne listeriosis have been caused by serotype 4b strains. Phylogenetic analysis of these three common clinical serotypes places them into two different lineages, with serotypes 1/2b and 4b … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
73
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 61 publications
3
73
0
2
Order By: Relevance
“…Lineage II includes serotype 1/2a, one of the most commonly found in foods (43,47,48,59), and it is possible that the sigC region contributes to physiological characteristics important to survival in the food production environment. Analysis of compositional bias in sigC and the adjacent lmo0422-lmo0421 region is consistent with the region being ancestral to the species and subsequently lost during the divergence of phylogenetic lineage I (65). Indeed, orthologous genes are also found in the Listeria innocua genome at the same relative position, further underscoring the conclusion that it is ancestral to the genus.…”
supporting
confidence: 57%
See 1 more Smart Citation
“…Lineage II includes serotype 1/2a, one of the most commonly found in foods (43,47,48,59), and it is possible that the sigC region contributes to physiological characteristics important to survival in the food production environment. Analysis of compositional bias in sigC and the adjacent lmo0422-lmo0421 region is consistent with the region being ancestral to the species and subsequently lost during the divergence of phylogenetic lineage I (65). Indeed, orthologous genes are also found in the Listeria innocua genome at the same relative position, further underscoring the conclusion that it is ancestral to the genus.…”
supporting
confidence: 57%
“…Based on phylogenetic analysis of genome composition, we have recently shown that a previously unknown sigma factorlike gene, lmo0423 (herein referred to as sigC), is part of a three gene region that is carried only by L. monocytogenes strains comprising phylogenetic lineage II of the species (65). Lineage II includes serotype 1/2a, one of the most commonly found in foods (43,47,48,59), and it is possible that the sigC region contributes to physiological characteristics important to survival in the food production environment.…”
mentioning
confidence: 99%
“…DNA subtyping with DNA microarrays may provide an improved alternative to resolve genetic differences that exist among isolates (4,9,28). This technique has the added advantage that, unlike PFGE, ribotyping, and MLST, it can identify specific or unique genes associated with strains of interest.…”
mentioning
confidence: 99%
“…Comparative whole-genome microarray hybridization has revealed differences in the contents of genes and genomic islands (GEIs) in closely related strains or species with different host ranges and virulence characteristics (11,15,17,22,23,25,29,35,44,52,55). The GEIs may contain bacteriophage and plasmid genes and are typically flanked on one side by a tRNA gene and on the other by an integrase gene (21).…”
mentioning
confidence: 99%